Getting close-ish: A corpus based exploration of -ish as a marker of approximation and vagueness - Matthias Eitelmann; Dagmar Haumann (Zeitschrift für Wortbildung)
This paper investigates the approximative nature of -ish, which takes its origin in de-adjectival adjectives in Middle English and from there spreads to -ish-derivatives from a wide array of bases, in terms of both categoriality and complexity. Drawing on data from the TV corpus, the paper charts the inventory of ‑ish-derivatives expressing approximative senses and zooms in on de-adjectival derivatives (largish, small-er-ish), de-numeral derivatives (fourth-ish, 2.8-ish), as well as on non-category changing -ish-formations (a few weeks-ish, nothingish). Building on both the diachronic trajectory of approximative ‑ish as of Middle English and the inventory of -ish-formations in the TV corpus, the paper proposes an approximation cline ranging from the earliest relational/associative senses of the suffix via similitudinal and genuinely approximative senses to incipient privative senses, (almost) all of which are attested in the data investigated.